Surgical treatment of sacrococcygeal pilonidal sinus with the Limberg transposition flap - Shams ul Bari (Innovative Journal of Medical and Health Sciences, 2020)
Background: Pilonidal sinus disease is a common condition usually affecting young individuals and has been conventionally treated by open excision technique. Rhomboid Limberg is a transposition flap that has been pleaded for treatment of this condition. Aim: To study the outcome of Rhomboid excision with Limberg flap closure for the treatment of Sacrococcygeal Pilonidal sinus. Material and Methods: The study was conducted prospectively in the department of surgery Skims Medical College Srinagar from March 2014 to February 2019 and total of 55 patients with primary or recurrent pilonidal sinus disease were studied. Results: The average operative time was 60 minutes (range 50-80 minutes) Postoperative stay of patients in the hospital was 3-4 days.The complications were seen in total of four patients which included Seroma and mild gaping of the wound in one patient each and dehiscence in two patients. None of the patients had recurrence till date.Conclusions: Rhomboid excision with Limberg flap transposition is an effective surgical technique for management of pilonidal sinus. Keywords: Pilonidal sinus, Limberg flap, rhomboid transposition flap, fasciocutaneous flap,